Preparation of reference standard extract of Lonicera hypoglauca Miq. with macroporous resin following a scale-up separation. Issue 8 (24th May 2021) - Zhong, Jia-Lun; Muhammad, Nadeem; Bian, Ping-Feng; Shan, Ying-Ying; Yan, Wei-Dong
ABSTRACT: Bench-scale and pilot-scale methods were developed for the separation of extracted caffeoylquinic acids (CQAs) also called reference standard extracts (RSE) from defined source Lonicerae species using macroporous resin. Various separation parameters of the process were optimized such as Lonicera hypoglauca Miq. batch No. 4, 75% ethanol as extraction solvent, SD3000 macroporous resin, 3 mg/mL of total CQA loading solutions, 2 BV/h of adsorption and desorption flow rates and ethanol-water (30:70, 80:20, v / v ) as eluent in gradient mode. The pilot-scale experiments were evaluated in six cycles. The quantitative analysis of CQA using RSE and mixed external standards were compared.